Clinical and molecular delineation of PUS3‐associated neurodevelopmental disorders. Issue 5 (31st August 2021) - Nøstvik, Miriam; Kateta, Sarah M.; Schönewolf‐Greulich, Bitten; Afenjar, Alexandra; Barth, Magalie; Boschann, Felix; Doummar, Diane; Haack, Tobias B.; Keren, Boris; Livshits, Ludmila A.; Mei, Davide; Park, Joohyun; et al.
Abstract: Biallelic variants in PUS3 have recently been recognized as a rare cause of neurodevelopmental disorders. Pseudouridine synthase‐3 encoded by PUS3 is an enzyme important for modification of various RNAs, including transfer RNA (tRNA). Here we present the clinical and genetic features of 21 individuals with biallelic PUS3 variants: seven new and 14 previously reported individuals, where clinical features of two were updated. The clinical and genetic information were collected through collaborations or by literature search. All individuals were characterized by the local clinicians and the gene variants were identified by next generation sequencing (NGS) based methodologies. The clinical picture was dominated by global developmental delay, epilepsy, hypotonia and microcephaly. Gray sclera, which has previously been suggested to be a characteristic feature of PUS3 ‐associated phenotypes, was reported in only seven individuals. The patients had some dysmorphic facial features, but a recognizable gestalt was not observed. In conclusion, homozygous and compound heterozygous PUS3 variants lead to a rare neurodevelopmental disorder. Further functional studies are necessary to understand involvement of PUS3 and tRNA biogenesis in normal and abnormal brain development. Abstract :